‘Freedom’ and ‘Social Responsibility’ of Social Media: Emerging Issues in the Indian Legal System - Tewari, Deeksha Bajpai; Gautam, Upma (Kathmandu School of Law Review, 2014)
The paper seeks to highlight the performance of social responsibility as regards the online social sites. The role of social networking sites as a replacement to the erstwhile ‘open access’ platforms of deliberations will also be addressed. This paper also analyses various laws regulating the freedom of speech and expression in this open, wide cyberspace. It advocates the need for redefining the basic concepts of ethics, morality, freedom, liberty, and responsibility, which form the basis of legal framework regulating this large contiguous cyberspace.